2018
DOI: 10.26681/jote.2018.020308
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Professionalism Among OT Students: The Culture of Professionalism

Abstract: Occupational therapy (OT) students are likely to experience generational differences when interacting with faculty and clients. Each generational group has a shared culture and unique set of experiences that influence their behavior, expectations, and perceptions surrounding professionalism. When teaching professionalism to OT students, the cultural underpinnings and influences related to generational groups and their differences become important considerations. This manuscript explores the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This precision concerning antecedents of the concept is in line with the idea of a developmental understanding of professionalism (Reiter et al, 2018;Robinson et al, 2012;Sullivan & Thiessen, 2015); some prerequisites must first be acquired and must influence the possibilities of occupational therapists to develop and implement professionalism in their practice.…”
Section: Professionalism As a Developmental Process: The Importance Of Antecedentsmentioning
confidence: 58%
See 4 more Smart Citations
“…This precision concerning antecedents of the concept is in line with the idea of a developmental understanding of professionalism (Reiter et al, 2018;Robinson et al, 2012;Sullivan & Thiessen, 2015); some prerequisites must first be acquired and must influence the possibilities of occupational therapists to develop and implement professionalism in their practice.…”
Section: Professionalism As a Developmental Process: The Importance Of Antecedentsmentioning
confidence: 58%
“…The analysis allowed one to understand that culture impacts on the antecedents, attributes, and consequences of professionalism. The literature proposes that different cultural aspects may influence professionalism such as the societal ( Wood, 2004 ), individual ( Davys et al, 2006 ; Wood, 2004 ), generational ( Reiter et al, 2018 ), or organizational ( Burford et al, 2014 ) aspects of culture. As an example, Reiter et al (2018) have suggested differences in how occupational therapists of “various generations interpret and display [professional] behaviours” (p. 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations